Higher education fatigue and its associated factors among healthcare undergraduates in post-COVID-19 - Wittayapun, Yuwadee; Polpanadham, Panicha; Palanuput, Thippawan; Khammaneechan, Patthanasak; A'la, Muhamad Zulfatul; Piya-amornphan, Nitita (Frontiers in Education, 2025)
IntroductionFatigue is a universal complaint among university students. It has contributed to poor academic outcomes and unhealthy conditions. The modification of teaching and learning modalities in response to the COVID-19 pandemic has been identified as a key contributor to increased fatigue among students, which is linked to rising mental health concerns in this population. These changes have also influenced students' health behaviors. Despite these challenges, online and hybrid classrooms have become increasingly prevalent due to their advantages. This study aimed to systematically assess fatigue and related health behavior issues among undergraduates in the context of educational disruptions.MethodsPurposive sampling was applied, and an analytical observational study was conducted among 1,108 undergraduate healthcare professional students, including those enrolled in nursing, physical therapy, and public health programs. The severity of fatigue, history of musculoskeletal complaints, body mass index, and daily sedentary time were assessed using self-administered questionnaires delivered via Microsoft forms, and correlation analyses were conducted among these variables.Results and discussionFatigue was commonly observed among students in post-COVID-19 learning, with online, face-to-face, and hybrid classroom settings, and its severity was also associated with higher musculoskeletal complaint and higher body mass index. In conclusion, university students are vulnerable to higher education-related fatigue, which may be linked to educational disruptions and lifestyle changes. They also face elevated risks of obesity and sedentary behavior. Moreover, fatigue was associated with students' self-reported health conditions, underscoring its multifaceted impact. Therefore, early detection of fatigue and continuous support through lifestyle modifications should be prioritized to promote both learning capacity and health among undergraduates.